Real time monitoring bivalve behavior - Witbaard, Rob; Fischer, Philipp (SEANOE, 2019)
ReMoBiB (remote monitoring of bivalve behavior). The project aimed at deploying a so called valve gape monitor and connect it to a underwater node to generate an continuous online accesible data stream of valve gape measurement. The project aimed to demonstrate the possibility to use shell valve gape as a bio-monitor in addition to monitoring of more traditional environmental monitoring techniques. At the same time we wanted to test the possibility to connect this equipment to the COSYNA underwater node at Helgoland. For this, the existing stand alone equipment developed by NIOZ had to be adapted to enable connection and data tranfer. The scientific aim of the project was to establish the relationship between shell gape (filtration activity) of Arctica islandica and environmental factors (Salinity, Temperature, Chlorophyll, light) at the southern limit of its distribution. This is done by collecting a continuous observational time series on shell gaping behaviour covering at least an entire year, while at the same time high resolution environmental data are being collected from the underwater node to which the gape recorder is connected. Within the project it is aimed to develop an online visualisation of real time valve gape activity on the NIOZ and AWI website as means to raise awareness about sea life among the broader public and show that the shells are living creatures reacting to their environment.On the longer term the online monitoring of the gaping behaviour of bivalves adds an extra dimension to environmental monitoring especially for ecological studies. Results are likely to illustrate the role of (extreme) environmental conditions on the feeding behaviour of individuals and the variation therein. It is anticipated that this project will lead to intensified cooperation and joint benthic ecological studies between NIOZ and AWI. Valve gape has been determined by measuring the electromagnetical field between two electronic coils glued on to the shell at the siphon side of the shell. The strength of the electromagnetic field between the coils is a measure for the distance that the coils are separated and thus how far the both valves are apart from each other. Valve gape is expressed as fraction open, i.e. for comparison of different animals the signals are rescaled to vary between 0 and 1. Valve gape opening has been measured with a ~1 second frequency. These ultra high resolution data have been saved and collected in data files representing 1 hour periods. For data analyses the "seconds" data have been aggregated to minute data by calculating the average valve gape in that minute.